RADIOLOGICAL OUTCOME OF TRANSPEDICULAR SCREWS FIXATION IN THE MANAGEMENT OF THORACOLUMBAR SPINE INJURY - ul Haq, Mian Iftikhar; Khan, Shahbaz Ali; Aurangzeb, Ahsan; Ahmed, Ehtisham; Bhatti, Sajid Nazir; Noman, Ali (Journal of Ayub Medical College Abbottabad, 2015)
Background: Traumatic fracture of the spine is a serious neurosurgical condition that has serious impact on the patient's quality of life. Thoracolumbar junction is the most common site of spinal injuries. The aims of management of thoracolumbar spinal fractures are to restore vertebral column stability, and to obtain spinal canal decompression. This ultimately leads to early mobilization of the patients. This study was conducted to compare preoperative and post-operative vertebral height, kyphotic angle and sagittal index in patients treated with pedicle screws and rods in thoracolumbar spine fractures. Methods: This cross-sectional study was conducted in the department of Neurosurgery, Hayatabad Medical Complex, Peshawar from 1st. February 2010 to 31st. July 2011. A total 161 patients with unstable thoracolumber spine fracture were included in this study. In these patients fixation was done through transpedicle screws with rods. Anteroposterior and lateral views X-rays of thoraco-lumbar spine were done pre and post operatively. Results: Out of 161 patients, 109 (67.7%) were males and 52 (32.3%) females. The age of patients ranged from 20 to 70 years (mean 42.2 years) with 71 (44.1%) in the age range of 31-40 years. Preoperative average vertebral height was 9.4194 mm while postoperative average was 19.642 mm. The mean kyphosis was 23.06° preoperatively. Immediately after surgery the average correction of kyphosis was 9.45°. The pre-operative average sagittal index was 19.38°, which was reduced to an average 5.41° post operatively. Conclusions: Transpedicular fixation for unstable thoraco-lumbar spinal fractures achieves a stable fracture segment with improvement of vertebral height, kyphotic angle and sagittal index. Hence, preventing the secondary spinal deformities. Keywords: Radiological outcome, Transpedicular screws fixation, thoracolumbar spine injury